Disputes and legal and territorial activism in defense of seeds in Argentina - Perelmuter, Tamara (2022)
This article problematizes the disputes over seeds in Argentina. Research advances on seed enclosure are included. Activism in defense of seeds is also analyzed, that is, all actions performed by different sectors, especially farmers and natives, for seeds to continue to be considered common goods. Two types of activism are identified: i) Legal, especially associated with the disputes over the modification of the Seed Act and ii) Territorial, which includes the practices of improvement, recovery, conservation, and exchange of local seeds.